Government Budget Deficit and Economic Growth: Evidence from Iraq 1980-2018 - Sabr, Saud; Ahmed, Younis; Khan, Twana (The Arab Journal of Administration, 2021)
In the recent economic literature, there has been a great deal of discussion about the impact of budget deficits on economic growth in both developed and developing countries. Many economists and other observers have viewed the budget deficits as harmful to the world economies. The supposed harmful impacts include high real interest rates, low savings and low rates of economic growth. This paper examines the real impact of budget deficits on economic growth in Iraq in the short and long term. A time series analysis has been used as a sample in view of the period between 1980 and 2018. The Autoregressive Distributed Lag (ARDL) model has been used for the regression analysis. The results show a weak positive impact from budget deficit on economic growth in the short term, but a strong negative impact from the accumulating budget deficit on economic growth in the long term.